Pedagogy of Social Studies Learning in Responding to Local, National and Global Inequalities - Nana Supriatna (Social Studies Conference Proceedings, 2022)
Pedagogy of Social Studies Learning in Responding to Local, National and Global Inequalities presented by Nana Supriatna